2013
DOI: 10.1182/blood-2013-05-504449
|View full text |Cite
|
Sign up to set email alerts
|

Platelets mediate increased endothelium permeability in dengue through NLRP3-inflammasome activation

Abstract: • Dengue infection triggers functional inflammasome assembly in platelets.• Platelets may contribute to increased vascular permeability in dengue virus infection by synthesis and release of IL-1b.Dengue is the most frequent hemorrhagic viral disease and re-emergent infection in the world. Although thrombocytopenia is characteristically observed in mild and severe forms of dengue, the role of platelet activation in dengue pathogenesis has not been fully elucidated. We hypothesize that platelets have major roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
386
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(405 citation statements)
references
References 46 publications
(69 reference statements)
13
386
1
5
Order By: Relevance
“…channel-mediated. IL-1b secretion from platelets plays a crucial role in increased human microvascular endothelial cell permeability in vitro and vascular permeability in clinical cases [65]. Further investigation regarding the mechanism of inflammasome activation by DENV demonstrated that C-type lectin domain family 5 members A (CLEC5A) interacts directly with DENV, triggering NLRP3 inflammasome activation [66].…”
Section: Rna Virusesmentioning
confidence: 99%
“…channel-mediated. IL-1b secretion from platelets plays a crucial role in increased human microvascular endothelial cell permeability in vitro and vascular permeability in clinical cases [65]. Further investigation regarding the mechanism of inflammasome activation by DENV demonstrated that C-type lectin domain family 5 members A (CLEC5A) interacts directly with DENV, triggering NLRP3 inflammasome activation [66].…”
Section: Rna Virusesmentioning
confidence: 99%
“…These were expressed in both leukocytes as well as activated endothelium, but also in selected neurons and even in platelets. 44 A large amount of reports define the role of TLRs in ischemic brain injury and neurodegenerative diseases, whereas the consequences of NLR-activation during brain injury are only partially understood up until now.…”
Section: Inflammasome: Intracellular Sensor For Danger Signals and Ismentioning
confidence: 99%
“…23 Local inflammation in atherosclerotic lesions is sustained by cholesterol crystal-induced activation of inflammasomes and platelets could increase the endothelium permeability through NLRP3 inflammasome activation. 44 Inflammasome deficiency reduces the immune barrier in the gut, modifies the microbiom and increases incidence of autoimmune diseases such as autoimmune colitis or hepatitis. NLR, NOD-like receptor.…”
Section: Inflammasome: Activators In Strokementioning
confidence: 99%
See 2 more Smart Citations